DISTRIBUTION OF HISTOPATHOLOGICAL TYPES AND PROGNOSTIC FACTORS FOR THYROID CARCINOMAS: NATIONAL SURVEY (1999-2015) - Makazlieva, Tanja; Vaskova, Olivija; Stojanoski, Sinisha; Manevska, Nevena; Velikj Stefanovska, Vesna (Karger, 2019)
Objectives: To present distribution of histhopathological types, survival rate and prognostic influence of four features: age, gender, initial lymph node involvement and histopathological type for survival rate in thyroid carcinomas (TC) diagnosed in Republic of North Macedonia during the period of 17 year (1999 – 2015). Material and methods: The retrospective analysis of medical data for TC diagnosed at national level from two main state thyroid departments during 1999 – 2015 was performed. The survival rate of alltypes of TC using Kaplan Meier method was estimated. Univariate Cox - proportional model was applied for evaluation of the predictors for survival rate. Results: A total number of 422 TC cases were diagnosed, with female/male ratio 3.5/1. Histopathology was available for 386 cases showing distribution of papillary TC in 79.5%, follicular TC in 10.9%, medullary TC in 4.2% and anaplastic TC in 3.1%. The mean survival time of all TC patients was 212.99 [95% CI (204.6 – 221,4)] months, with longest mean survival time for papillary TC –223.07 [95% CI (218.6 – 227,5)] months; for follicular TC – 161 [95% CI (138.8 – 184.7)] months; medullary TC – 179 [95% CI (155.5 – 203.3)] months and for anaplastic TC 22.3 [95% CI (10.2 – 34.4)] months. Age, initial lymph node involvement and histopathology were selected by Cox -proportional model as independent significant predictors for survival. Conclusion: During a survey period, our study revealed continuous increase in TC cases, with papillary TC as most common type. There was an excellent overall prognosis of TC at national level. Age, histopathological type and initial lymph node involvement were found as significant independent prognostic predictive features for survival rate in the evaluated patients. Further evaluation of prognostic influence of different therapy protocols used during analyzed period should be performed.